2007
DOI: 10.21273/jashs.132.5.638
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Concentration and Browning Susceptibility in a Collection of Different Varietal Types and Hybrids of Eggplant: Implications for Breeding for Higher Nutritional Quality and Reduced Browning

Abstract: Phenolic compounds have numerous beneficial effects on human health. In consequence, the development of new varieties with higher content of phenolics is of interest for the improvement of the nutritional quality of eggplant (Solanum melongena L.). However, the oxidation of eggplant phenolics causes browning of the cut surfaces of the fruit and reduces its apparent quality. The authors investigated the relationship among, as well as the variation and heritability of, the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
121
3
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(151 citation statements)
references
References 28 publications
19
121
3
5
Order By: Relevance
“…Measurements of fruit phenolics content in the parental lines confirms the occurrence of low total fruit phenolics in S. aethiopicum relative to S. melongena (Stommel and Whitaker 2003;Prohens et al 2007;Mennella et al 2010) and denote that S. melongena could be utilized for improving the phenolics content of S. aethiopicum. Low fruit phenolics in interspecific hybrids suggests dominance of the S. aethiopicum alleles.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Measurements of fruit phenolics content in the parental lines confirms the occurrence of low total fruit phenolics in S. aethiopicum relative to S. melongena (Stommel and Whitaker 2003;Prohens et al 2007;Mennella et al 2010) and denote that S. melongena could be utilized for improving the phenolics content of S. aethiopicum. Low fruit phenolics in interspecific hybrids suggests dominance of the S. aethiopicum alleles.…”
Section: Discussionsupporting
confidence: 52%
“…0°20 0 11 00 W) in a completely randomized design. A completely randomized design was used instead of a block design because the plot is quite uniform and previous experiments using block designs showed no block effect (Prohens et al 2007;Muñoz-Falcón et al 2008). Plants were spaced 1 m between rows and 0.8 m apart within the row and drip irrigated.…”
Section: Growing Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Color changes are likely due to the onset of enzymatic browning triggered by the grinding. Prohens, Rodríguez-Burruezo, Dolores Raiǵ on, and Nuez (2007) showed that there were significant correlations amongst phenolics, color difference, and degree of browning. Nicoli, Calligaris, and Manzocco (2000) reported that browning was associated with a decrease in antioxidant activity of apples.…”
Section: Effect Of Grinding On Appearance Degree Of Browning and Antmentioning
confidence: 97%